1998
DOI: 10.1159/000020560
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor: How It Transmits Its Signal

Abstract: Vascular endothelial growth factor (VEGF) is an essential molecule in the development and formation of mammalian blood vessels in health and disease. VEGF is also increasingly implicated in other biological processes including renal development and pathophysiology. The biological activities of VEGF in vivo and in its target cells in culture are mediated through two receptor protein tyrosine kinases, KDR/Flk-1 and Flt-1. KDR/Flk-1 is able to mediate the tyrosine phosphorylation of several cellular components as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…In the early stage, in addition to the abnormalities of hypertrophic podocytes discussed, high levels of VEGF derived from podocytes can strongly bind to capillary endothelial cells through specific VEGF receptors, which may result in increased permeability or glomerular hyperfiltration by altering capillary fenestration or basement membrane components 26 or indirectly through the induction of nitric oxide and prostacyclin. 27 In our study, we found that many endothelial cells in glomeruli showed subendothelial edema (Figure 7C). It has been reported that VEGF stimulates increased synthesis of collagenase by endothelial cells, which would result in the proteolytic disruption of the basement membrane.…”
Section: Vegf and Proteinuriasupporting
confidence: 52%
“…In the early stage, in addition to the abnormalities of hypertrophic podocytes discussed, high levels of VEGF derived from podocytes can strongly bind to capillary endothelial cells through specific VEGF receptors, which may result in increased permeability or glomerular hyperfiltration by altering capillary fenestration or basement membrane components 26 or indirectly through the induction of nitric oxide and prostacyclin. 27 In our study, we found that many endothelial cells in glomeruli showed subendothelial edema (Figure 7C). It has been reported that VEGF stimulates increased synthesis of collagenase by endothelial cells, which would result in the proteolytic disruption of the basement membrane.…”
Section: Vegf and Proteinuriasupporting
confidence: 52%
“…VEGFR-2 appears to be the most important receptor in VEGF-induced mitogenesis and permeability (Waltenberger et al, 1994;Zachary, 1998). It has a lower affinity for VEGF-A (K d ϭ 400 -800 pM) than VEGFR-1 (Terman et al, 1994).…”
Section: B Vascular Endothelial Growth Factor Receptorsmentioning
confidence: 99%
“…Vascular ENLXDTHELiAL growth factor (VEGF) is a Compelling evidence has shown that VEGF is critical for dimeric heparin-binding protein and the most imporgrowth of solid tumors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Without new blood vessel fortant growth factor for endothelial cells of the arteries, veins, mation, solid tumors are limited to a few millimeters in size, and lymphatics (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%